(untitled) (Swiss Medical Weekly, 2014)
Conducting clinical studies in the paediatric population is complex and difficult. Paediatricians deal with a vulnerable population, which primarily needs protection and where patient numbers are always low. In addition, the pharmaceutical industry often demonstrates lack of interest due to the small and non-rewarding market. Public awareness for the need of paediatric research is likewise limited. This results in lack of funding for academic studies. In Switzerland, there is a new initiative that strives to overcome the given barriers and hurdles. SwissPedNet is still in a start-up phase, but it is now ready for all collaborations of interest and keen to work together with all stakeholders on the medical progress and improvement of paediatric clinical research with the overall goal of implementing evidence-based medicine for our children (www.swisspednet.ch).